MONAS (MONOPOLI ASLI INDONESIA) SEBAGAI MEDIA BERMAIN UNTUK MEMBENTUK KARAKTER ANAK CINTA INDONESIA - Novalita, Yolanda; Rahmawati, Apriana; Qowi, Nurul Hikmatul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Currently, limited number of children, in particular those who live in big cities, are playing traditional game as one of Indonesianâs culture. This study proposes the so called MONAS (Monopoli Asli Indonesia) as a media for playing to form good character. MONAS uses three dimensions using development psychology method. The making of MONAS follows some steps, namely collecting, designing, printing, arranging, perfecting, and evaluating.The monopoly game is compiled in one package. The package has three dimensions of which there are 155 note of moneys in seven nominal, one piece of question and answer, 30 cards of DOORPRIZE and ZONK, 1 piece of game rule, 5 dummies, 33 villas and motels. The proposed monopoly game is believed to provide motivation for creating the feeling of loving Indonesia culture so they donât have to leave our traditional game.